A High-Molecular-Mass Surface Protein (Lsp) and Methionine Sulfoxide Reductase B (MsrB) Contribute to the Ecological Performance of Lactobacillus reuteri in the Murine Gut - Walter, Jens (American Society for Microbiology, 2005)
Members of the genus Lactobacillus are common inhabitants of the gut, yet little is known about the traits that contribute to their ecological performance in gastrointestinal ecosystems. Lactobacillus reuteri 100-23 persists in the gut of the reconstituted Lactobacillus-free mouse after a single oral inoculation. Recently, three genes of this strain that were specifically induced (in vivo induced) in the murine gut were identified (38). We report here the detection of a gene of L. reuteri 100-23 that encodes a high-molecular-mass surface protein (Lsp) that shows homology to proteins involved in the adherence of other bacteria to epithelial cells and in biofilm formation. The three in vivo-induced genes and lsp of L. reuteri 100-23 were inactivated by insertional mutagenesis in order to study their biological importance in the murine gastrointestinal tract. Competition experiments showed that mutation of lsp and a gene encoding methionine sulfoxide reductase (MsrB) reduced ecological performance. Mutation of lsp impaired the adherence of the bacteria to the epithelium of the mouse forestomach and altered colonization dynamics. Homologues of lsp and msrB are present in the genomes of several strains of Lactobacillus and may play an important role in the maintenance of these bacteria in gut ecosystems.